Synthesis of hypercoordinated silicon species and asymmetric radical reaction via chiral ion-pairing - Millanvois, Alexandre (Nanyang Technological University, 2025)
Since 2014, Prof. Fensterbank and Dr. Ollivier have studied the use of hypercoordinated silicon species silicate as radical precursors under photocatalyzed conditions. The classical cation used by our laboratory is mainly a chelated potassium with crown-ether, to prevent high molecular mass and resulting a poor atom economy when employed in organic synthesis, synthesis and study of several alkali derivative was done. Their synthetic pathway has permitted to reach new alkali derivatives (Li, Na, K) with several substituent. Their physical properties were studied (NMR, cyclic voltammetry, X-Ray) and compared with the already known silicates. Their use as radical precursors in a dual nickel/photoredox methodology was then developed and published. During our study oriented on the synthesis of these derivatives, we provided an overview on the synthesis of bis(catecholato)silicate and published a review on this topic. In addition, we published more specific reviews regarding the use of hypercoordinated species in our laboratory and organometallic/photoredox catalysis. Owing to the limitations in commercially available trialkoxysilanes, we have investigated the synthesis of some silane derivatives, mainly substituted by cyclopropane or fluorinated alkyl chain, to access nontrivial radicals. The recent use of Martin’s spirosilicates as radical precursor has allowed the synthesis of new potential precursors on this hypercoordinated derivative.The development of these cyclopropane alkoxysilanes was achieved in gram scale, as well as the synthesis of the corresponding bis(catecholato)silicates. The methodology involved commercially available vinyl silane engaged in a formal [2+1] cycloaddition and our classical methodology to reach hypercoordinated species selectively. Indeed, the preparation of silicates led to the formation of pentavalent silicons bearing the cyclopropyl both known to act as radical precursors under oxidative condition. Early results show a lack of reactivity concerning the generation of cyclopropyl radical from hypercoordinated silicon species. The desired silicate was not achieved but interesting results were obtained with the Martin’s silicate. The observation of the desired -CF3 ; species and later isolation of the -C2F5 one were achieved. The oxidation of the pentafluorosilicate was unsuccessful and the inability of the silicon species to act as radical precursor was rationalised. The nucleophilic behaviour on those silicon species was finally observed in solution at the cesium fluoride interface between and in solid-state under mechanochemical conditions. The mechanism of the reaction was studied and mechanistic insights were obtained by DFT calculations. (The manuscript on this work is currently in preparation we have questioned the ability of these anionic radical precursors with several small cations to be employed in a phase transfer reaction using chiral guanidinium derivative. This topic would later be extended to classical anionic radical precursors (R-BF3K, carboxylate, anionic single electron donor..) with the idea of controlling radical species using the chiral ion-pair strategy. During our study, we have found that anionic salts, such as potassium 2-nitropropane salt or thiolate, act as single electron donor performing some radical reaction inside the chiral catalyst’s pocket. This work was done in direct collaboration with Dr. Ban Xu in NTU. My work involved the design and investigation about the mechanistic part for this project. Interestingly, we were able to perform this reaction in solution and solid state under mechanochemical conditions allowing us to reach high yield and high enantioselectivity. The mechanistic study has showed similitude between both medium and has allowed us to propose a mechanism for this methodology. Finally, the solid-state oxidation of several radicals precursors (trifluoroborate, pentafluorosilicate and silicate was investigated using organic and inorganic oxidants.